Nutritional Status Measures Are Correlated with Pupillary Responsiveness in Zambian Children. Issue 7 (19th June 2018) - Healy, Katherine; Palmer, Amanda C; Barffour, Maxwell A; Schulze, Kerry J; Siamusantu, Ward; Chileshe, Justin; West, Keith P; Labrique, Alain B
Abstract: Background: Impairments in visual function have been well characterized in vitamin A deficiency. However, eye function may also be sensitive to other nutrient deficiencies. Objective: We examined associations between visual function—characterized by pupillary threshold or pupillary responsiveness—and nutritional status in Zambian children. Methods: We used digital pupillometry to measure visual responses to calibrated light stimuli (−2.9 to 0.1 log cd/m 2 ) among dark-adapted children aged 4–8 y ( n = 542). We defined pupillary threshold as the first light stimulus at which pupil diameter decreased by ≥10% and considered a pupillary threshold ≥−0.9 log cd/m 2 as impaired. Pupillary responsiveness was defined by absolute percentage of change in pupil diameter from pre- to poststimulus. We tested associations between these measures and serum concentrations of retinol, β-carotene, ferritin, soluble transferrin receptor, and hemoglobin (Hb <11.0 or 11.5 g/dL were used to define anemia, depending on age), as well as anthropometric indexes, with the use multilevel mixed-effects models. Results: Pupillary threshold was correlated only with serum retinol ( r = 0.12, P < 0.05). The strongest correlates of pupillary responsiveness were Hb ( r = −0.16, P < 0.01), height-for-age z score ( r = 0.14, P < 0.05), weight-for-age z score ( r = 0.14, P < 0.05), and soluble transferrin receptor ( r = 0.12, P < 0.05). In multivariate models, anemia was positively associated with pupillary responsiveness (β = 2.99; 95% CI: 1.26, 4.72). Conclusions: In this marginally nourished population, we found positive correlations between vitamin A status, iron status, or anthropometric indexes and visual function. Hb was negatively associated with visual function, with greater pupillary responsiveness among anemic children. We posit that this may signal altered parasympathetic activity, possibly driven by infection. Future studies should consider a broader range of indicators to better characterize the relation between nutrition and visual function. This trial was registered at clinicaltrials.gov as NCT01695148.